Efektivitas Pemberian Pupuk Kandang Kotoran Kambing dan Trichoderma Terhadap Pertumbuhan dan Hasil Tanaman Timun Apel (Cucumis melo L.) - Sihombing, Vinsensius Evando; Muharam, Muharam; Muhammad B, Fawzy (UNIVERSITAS LABUHANBATU, 2024)
The use of organic matter to increase the growth and yield of apple cucumber plants. The research was carried out in Pasirjengkol Village, Majalaya District, Karawang Regency from March 2023 to May 2024. The method used was a single-factor Group Random Design (RAK) with 7 treatments, 4 replicates and 2 plant samples, so that there were 56 experimental units consisting of: A (control), B (Goat manure 20 tons/hectare + Trichoderma 15 g/plant), C (Goat manure 20 tons/hectare + Trichoderma 20 g/plant), D (Goat manure 20 tons/hectare + Trichoderma 25 g/plant), E (Goat manure 40 tons/hectare + Trichoderma 15 g/plant), F (Goat manure 40 tons/hectare + Trichoderma 20 g/plant), G (Goat manure 40 tons/hectare + Trichoderma 25 g/plant). The results of the experiment were tested with the F test, if it had a real effect, it was further tested by the Duncan Multiple Range Test (DMRT) at the level of 5%. The results showed that the treatment had a real effect on plant growth and yield. G treatment (Goat manure 40tons/hectare + Trichoderma 25 g/plant) gave the highest yields for tendril length (137.875cm), stem diameter (3.575 mm), number of leaves (47 pieces), fruit weight (128.35 grams), number of fruits (5 pieces), and fruit sweetness (13.85 brix). Keywords: goat manure, trichoderma, apple cucumber